The Effectiveness of Problem Based Learning Model Combined with Talking Stick on IPAS Learning Outcomes - Isnaeni Mulyaningtyas; Farid Ahmadi (Jurnal Penelitian Pendidikan IPA, 2024)
The objective of this study was to examine the effectiveness of Problem-Based Learning model combined with talking stick on IPAS learning outcomes. This research is experimental and uses a quantitative approach. The study design is quasi-experimental, utilizing a nonequivalent control group design. The study population consisted of fourth-grade students at SD Gugus Kemuning in Semarang City. The samples of this study were fourth-grade students of SDN Wonosari 02 and SDN Wonosari 03. Normality, homogeneity, t-test, and N-gain tests were used to analyze the data. The results showed that the Problem Based Learning model combined with talking stick is more effective in improving the IPAS learning outcomes compared to the conventional learning model. The t-test results demonstrate a significant difference between the IPAS learning outcomes before and after treatment, as evidenced by the t value > t table (9.00 > 2.05 and 11.10 > 2.05). This is also corroborated by the experimental class N-gain test results, which are 0.56 and 0.53 greater than the control class, respectively, at 0.29 and 0.24.